Improving the learning outcome of peer-feedback sessions - Harloff-Helleberg, Stine (Improving University Science Teaching and Learning, 2023)
This work is based on an elective course at master level qualifying for 7.5 ETCS. It comprises 32 lectures, 64 hours of class instruction, and 110 hours allocated to preparation e.g. group work. Here, the students work in groups of three to prepare three deliverables throughout the course e.g. 1) oral presentation of a case-study, 2) 2-3 written laboratory journals including presentation hereof, and 3) poster presentation on their case. The students give and receive formative peer-feedback on each deliverable e.g. oral feedback on deliverable 1 and 3, whereas they receive both oral and written peerfeedback on deliverable 2. In addition to the peer feedback, the students also receive feedback in plenum from the course responsible. Course capacity is 60 students, with an average of 20 students enrolled per course. The exam is based on a continuous assessment by the course directors. This year, only 9 students participated in the course due to unforeseen circumstances. I share the role as course director with a college, with whom I designed and planned this course in 2018. Each year, student feedback is used to further develop the course striving at increased learning outcome.